2004
DOI: 10.1007/s00436-004-1127-3
|View full text |Cite
|
Sign up to set email alerts
|

Tegumental surface changes in adult Fasciola hepatica following treatment in vitro and in vivo with an experimental fasciolicide

Abstract: Our objective was to determine by scanning electron microscopy the structural changes in the tegument of adult Fasciola hepatica after treatment with 5-chloro-2-methylthio-6-(1-naphtyloxy)-1 H-benzimidazole, called compound alpha, and its active metabolite sulphoxide, under in vitro and in vivo conditions. For the in vitro studies, flukes from sheep were exposed to 40 mg/l of compound alpha-sulphoxide over different incubation times. Flukes for the in vivo studies were raised in sheep treated orally with compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
4
17
1
Order By: Relevance
“…The dorsal surface showed a similar disruption to the ventral surface and the posterior region was more severely disrupted than the anterior part. The findings are similar to the effects of praziquantel (Apinhasmit & Sobhon, 1996), albendazole sulphoxide (Buchanan et al, 2003), and 5-chloro-2-methylthio-6-(1-naphthyloxy)-1-H-benzimidazole (Rivera et al, 2004(Rivera et al, , 2005. The regional differences in damage may be due to tegumental structure, route of drug uptake and drug metabolism (McKinstry et al, 2003).…”
Section: Discussionsupporting
confidence: 72%
“…The dorsal surface showed a similar disruption to the ventral surface and the posterior region was more severely disrupted than the anterior part. The findings are similar to the effects of praziquantel (Apinhasmit & Sobhon, 1996), albendazole sulphoxide (Buchanan et al, 2003), and 5-chloro-2-methylthio-6-(1-naphthyloxy)-1-H-benzimidazole (Rivera et al, 2004(Rivera et al, , 2005. The regional differences in damage may be due to tegumental structure, route of drug uptake and drug metabolism (McKinstry et al, 2003).…”
Section: Discussionsupporting
confidence: 72%
“…AJPS are also caused by the effect of commercial fascioliscide; it can therefore be assumed that these extracts can cause similar effects [20][21][22]. With regard to the other fragments (ethyl acetate and methanol) no notorious fascioliscide activity was detected, since very limited activity (10%) was demonstrated during the testing of the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…It has been firmly documented that one of the hallmark effects of any anthelmintic is the destruction of the worm's surface. This is due to the fact that the tegumental and/or cuticular structures are the primary parasite-host interfaces, vital for absorption of nutrients and perception of the surrounding micro-environment provided by the host (William et al 2001;Mckinstry et al 2003;Rivera et al 2004;Xiao et al 2004;Roy et al 2008). Histological studies have revealed that anthelmintic agents induce considerable changes in the internal structural features of helminths, resulting in loss of normal cellular conformity in vital tissues (Roy et al 2008;Dasgupta et al 2010).…”
Section: Discussionmentioning
confidence: 99%